Integrated psychosocial and food security approach in an emergency context: Central African Republic. Issue 3 (November 2016) - Dozio, Elisabetta; Peyre, Lisa; Morel, Sophie Oliveau; Bizouerne, Cécile
Abstract : In the Central African Republic, a political crisis started in 2013 that greatly affected the population. They were exposed to traumatogenic factors causing the emergence of symptoms of posttraumatic stress disorder in large segments of the population. The situation of high food insecurity, combined with high levels of psychological distress, have significantly limited the population's coping strategies. Within this context, the nongovernmental organisation, Action Contre la Faim, implemented a programme aimed at addressing both immediate and underlying causes of malnutrition, integrating psychosocial and food security approaches. In order to improve the access to food, 900 pregnant and lactating women received monthly food coupons that were exchangeable in the local market. Of these, 199 women who had been identified as the most psychologically vulnerable benefited from specific support: individual counselling or therapeutic groups. Through this multi-sectoral approach, the women's average individual dietary diversity score increased and households improved their food consumption score. Further, these women improved their psychological wellbeing and were able to regain some degree of hope and to develop coping skills. They regained confidence and felt stronger and more prepared to face the future, showing that this multi-sectoral approach strengthened family resilience.